Galician language’s figures today: comments on the survey about the knowledge and use of Galician (2010) - Muñoz Carrobles, Diego (Madrygal. Revista de Estudios Gallegos, 2011)
In this paper we are going to make a general comment on the results arosen from the survey about knowledge and use of Galician language, directed by the Galician Institute for Statistics. We will try to present, explain and analyze these figures taking into account some recent publications and other important sociolinguistic data; we will also have a look at the sociolinguistic evolution, by comparing these results with the ones from 2003.